Synthesis and characterization of some New Derivatives from 2- Mercaptobenzothiazole - Ahmad, Mohammad; Ahmad, Athraa (Iraqi Journal of Science, 2023)
In this work 2- mercaptobenzothiazole ( 2-MBT ) and some of its derivatives(1, 14 ,27) were prepared by using home made Auto clave .The synthesis involve treatment of 2- MBT or some of its derivatives with chloro acetyl chloride to give 1- chloro acetyl -2- MBT or the corresponding derivatives (2,15,28) . the product was treated with phenyl hydrazine to give the phenyl hydrazide derivatives (3,16,29) . The new derivatives(4-13, 17-26,30-39) were synthesized by reaction of the phenyl hydrazide derivatives with different aromatic aldehydes in the presence of Acetic Acid . Structure of all the prepared compounds confirmation were proved using FTIR , elemental analysis (C .H .N .S ) in addition to melting points.